Automatic generation of semantic knowledge networks from an unstructured text - Savchenko, M.N.; Kriachok, A.S. (Управляющие системы и машины, 2018)
A method and an algorithm for the semantic knowledge network automated construction created from the most informative concepts in the electronic texts are proposed. Аn analysis and comparison of existing methods with their software implementations for information research in electronic texts are presented. The results of BBC news article analysis using the proposed method are given.